Postcolonialism Unveiled: At the Nexus of Scientific Inquiry and Political Discourse - R. Tempest (Международная аналитика)
Richard Tempest is a Professor of Slavic Languages and Literatures at the University of Illinois, Urbana-Champaign, and a former director of its Russian, East European, and Eurasian Center. He holds a BA (First Class), MA, and PhD from the University of Oxford. His interests include Russian and world history and culture, military history, and the political science of the body. Tempest is the author of “Overwriting Chaos: Aleksandr Solzhenitsyn’s Fictive Worlds” (Boston: Academic Studies Press, 2019). Currently, Tempest is researching a monograph on the politics of charisma in the twenty-ﬁrst century.The conversation was conducted by Sergey Markedonov, Editor-in-Chief of the Journal of International Analytics.